2022
DOI: 10.5194/npg-29-301-2022
|View full text |Cite
|
Sign up to set email alerts
|

Integrated hydrodynamic and machine learning models for compound flooding prediction in a data-scarce estuarine delta

Abstract: Abstract. Flood forecasting based on hydrodynamic modeling is an essential non-structural measure against compound flooding across the globe. With the risk increasing under climate change, all coastal areas are now in need of flood risk management strategies. Unfortunately, for local water management agencies in developing countries, building such a model is challenging due to the limited computational resources and the scarcity of observational data. We attempt to solve this issue by proposing an integrated h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Using the Variant Inflation Factor, Sampurno et al conducted a statistical analysis to analyze the multicollinearity between the predictor variables (Sampurno, Vallaeys, Ardianto, & Hanert, 2022). The researcher tested four kernels, namely linear, polynomial, radial basis, and sigmoid, and found that the radial kernel had the best performance in the SVM algorithm.…”
Section: Literature Study Related Flood Prediction Using Other Methodsmentioning
confidence: 99%
“…Using the Variant Inflation Factor, Sampurno et al conducted a statistical analysis to analyze the multicollinearity between the predictor variables (Sampurno, Vallaeys, Ardianto, & Hanert, 2022). The researcher tested four kernels, namely linear, polynomial, radial basis, and sigmoid, and found that the radial kernel had the best performance in the SVM algorithm.…”
Section: Literature Study Related Flood Prediction Using Other Methodsmentioning
confidence: 99%
“…Chondros (2021) proposed an integrated approach for flood warning applicable to the flood-prone coastal area of Rohimno, Crete, Greece, developing an ANN model and demonstrating the superior performance of the developed ANN [146]. In addition to ANNs, other ML models-such as random forests (RF) [147][148][149][150][151], the Gaussian process metamodel (GPM) [152], support-vector machine (SVM) [147,150], and recurrent neural networks (RNNs) [153]-have also been applied. The ML model can make full use of historical data without considering the physical process of flood formation and can quickly train, verify, test, and evaluate the risk of floods based only on the historical flood record dataset, which provides an easier-to-implement approach to flood prediction, with high performance and relatively little complexity compared to physical models [154].…”
Section: Integrated Hazard Risk Mappingmentioning
confidence: 99%
“…The combination of hydrodynamic models and machine learning can improve analysis reliability and computational efficiency [157,158]. For example, his-torical data or simulated data from hydrodynamic models can be used to train machine learning models to predict wave heights [159,160], hurricane storm surge hazards [161,162], floods [163], erosion [164], and water level characteristics of storm surges [155]. Notably, a nearshore wave and hydrodynamic prediction model by Wei and Davison [165] based on Convolutional Neural Networks can accurately predict the propagation and fragmentation of waves on nearshore slopes, including detailed wave peak bending and separation.…”
Section: Prediction Of Water Quality Through Coupling Hydrodynamics A...mentioning
confidence: 99%